2016
DOI: 10.1002/jlcr.3372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and biological evaluation of new biotinylated 99mTc/Re‐tricarbonyl complexes

Abstract: The synthesis and biological evaluation of three new biotinylated fac-[(99m)Tc/Re(CO)3](+) complexes with the tridentate ligands L1, L2, and L3 are reported. L1-L3 contain the chelators 2-((5-aminopentyl)(pyridin-2-ylmethyl)amino)acetic acid, 2-(2-aminoethylthio)-3-(1H-imidazol-4-yl)propanoic acid, and 2-amino-3-(1-carboxy-2-(1H-imidazol-4-yl)ethylthio)propanoic acid, respectively, which are conjugated to biotin's carboxylate via their amine group. The fac-[Re(CO)3(L1-L3)] complexes were synthesized and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This result concurs with the stability of the radiotracer in serum at 37°C in vitro . As reported in a previous study, another chlorambucil derivative was synthesized by conjugating an NNO chelating group [N‐(3‐(dimethylamino)propyl)amido]acetic acid to chlorambucil, which was further labeled with 99m Tc(CO) 3 successfully. The in vivo biological studies of the reported 99m Tc(CO) 3 ‐labeled chlorambucil derivative showed increasing uptake in the stomach with the time (increasing from 3.07% ID/g at 1 h to 17.7% ID/g at 3 h), indicating that this radiotracer took place an in vivo decomposition even though it was very stable (98% RCP) in vitro experimental study under 37°C incubation in PBS at pH 7.0 as well as in human serum .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result concurs with the stability of the radiotracer in serum at 37°C in vitro . As reported in a previous study, another chlorambucil derivative was synthesized by conjugating an NNO chelating group [N‐(3‐(dimethylamino)propyl)amido]acetic acid to chlorambucil, which was further labeled with 99m Tc(CO) 3 successfully. The in vivo biological studies of the reported 99m Tc(CO) 3 ‐labeled chlorambucil derivative showed increasing uptake in the stomach with the time (increasing from 3.07% ID/g at 1 h to 17.7% ID/g at 3 h), indicating that this radiotracer took place an in vivo decomposition even though it was very stable (98% RCP) in vitro experimental study under 37°C incubation in PBS at pH 7.0 as well as in human serum .…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo biological studies of the reported 99m Tc(CO) 3 -labeled chlorambucil derivative showed increasing uptake in the stomach with the time (increasing from 3.07% ID/g at 1 h to 17.7% ID/g at 3 h), indicating that this radiotracer took place an in vivo decomposition even though it was very stable (98% RCP) in vitro experimental study under 37°C incubation in PBS at pH 7.0 as well as in human serum. 20 The difference might originate from the different tridentate chelating moieties. In our study, the tridentate ligand 2,2′dipicolylamine (DPA) was chosen as the chelating scaffold, which exhibited favorable complexation property and kinetic stability with the fac-[M I (CO) 3 ] + core.…”
Section: Biodistribution In Tumor-bearing Micementioning
confidence: 99%
See 2 more Smart Citations